1984
DOI: 10.7863/jum.1984.3.7.289
|View full text |Cite
|
Sign up to set email alerts
|

The inaccuracy of total uterine volume measurements: sources of error and a proposed solution.

Abstract: Inaccuracies in total intmuterine volumes calculated using the prolate el~ lipse equation have been reported. No previous study has examined all the sources of error. In this study, a comprehensive approach was undertaken. Measurements were obtained from scans of the pregnant uterus in the prone position using an automated water-path scanner (Octoson) and in the supine position using standard static B-mode scanners. Several conclusions could be drawn : 1) From the Octoson prone scans, uterine volumes obtained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

1985
1985
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 7 publications
0
15
0
Order By: Relevance
“…5 When the uterine volume is more than indicated for vaginal hysterectomy but the surgeon feels that a vaginal route may succeed, a trial vaginal hysterectomy (similar to trial forceps delivery in obstetrics to avoid opening the abdomen in a well-counseled obstetric patient) should be planned, with facilities for laparoscopic assistance or cesarean section available. 4,6 When uterine volume exceeds 240-350 cm 3 , trial vaginal hysterectomy is favored or laparoscopic technique considered. One of the authors of this paper is used to performing vaginal hysterectomy on a contraindicated enlarged uterus and comfortably accepts the vaginal route for uterine volumes of 500-800 cm 3 as trial vaginal hysterectomy cases; if these fail vaginally, laparoscopic assistance or opening of the abdomen is utilized.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…5 When the uterine volume is more than indicated for vaginal hysterectomy but the surgeon feels that a vaginal route may succeed, a trial vaginal hysterectomy (similar to trial forceps delivery in obstetrics to avoid opening the abdomen in a well-counseled obstetric patient) should be planned, with facilities for laparoscopic assistance or cesarean section available. 4,6 When uterine volume exceeds 240-350 cm 3 , trial vaginal hysterectomy is favored or laparoscopic technique considered. One of the authors of this paper is used to performing vaginal hysterectomy on a contraindicated enlarged uterus and comfortably accepts the vaginal route for uterine volumes of 500-800 cm 3 as trial vaginal hysterectomy cases; if these fail vaginally, laparoscopic assistance or opening of the abdomen is utilized.…”
Section: Discussionmentioning
confidence: 99%
“…The uterine length (L) was defined as the distance between the internal orifice of the uterus (os) to the dome of the fundus and the maximum width (W) and anteroposterior (AP) diameter were taken perpendicular to the axis of the uterine length. Kurtz et al found that the prolate ellipse formula was not ideal for uterine volume calculation …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, the CV was approximated as a sphere in this study for the following reasons:1) The formula for a prolate ellipse volume has been called inaccurate by Kurtz et a1. 22 2) When these two methods of calculating volumes were compared by using four masses of modeling clay of known volumes (in the shape of a flat-sided prolate ellipsoid), the spherical volumes were about 90% of the true volumes, and the prolate ellipsoid volumes were about 80% of the true volumes. Thus, the spherical volumes more closely approximated the true volumes.…”
Section: Fetal Calvarial Volumementioning
confidence: 99%